Disaster of Retrobulbar Hemorrhage: Poster Presentation - Case Report - Resident - AMELIA DEVY INDRIASARI; Purjanto Tepo Utomo; Agus Supartoto; Banu Aji Dibyasakti; Irene Titin Darajati; Datu Respatika (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retrobulbar hemorrhage is a rare case, 3.6% of which are caused by ocular trauma. However, this case is an ophthalmic emergency and must be treated quickly and accurately. We present a case of neglected traumatic retrobulbar hemorrhage with compartment-syndrome and opportunistic bacterial infection which underwent dilemmatic exenteration and orbitectomy. Case Illustration : A 39-year-old man was referred with a history of being beaten, 11 days before admission. He felt a dark vision, pain and swelling in his left eye. The visual acuity was no light perception. Eyelid necrosis with proptosis and periorbital edema. We found severe chemosis and cloudy cornea. Negative-light reflex with increase intraocular pressure and limited eye movement in all directions. We did three surgeries due to serious complication. First, evacuation of retrobulbar bleeding. The second was total exenteration. The last was left orbitectomy, necrotomy and reconstruction performed together with plastic-surgeon and neuro-surgeon. Patient was hospitalized for 1.5 months. Discussion : Accumulation of blood in retrobulbar space leads to increased orbital pressure, which can stretch the optic nerve and impair blood flow in the eye which can lead to orbital compartment-syndrome. Unwanted complications can be prevented with prompt treatment within the first-two hours. Orbital decompression with lateral canthotomy and inferior cantholysis is considered as an emergency procedure. In this case, our patient had chronic compartment-syndrome and had no previous orbital decompression. Conclusion : Retrobulbar hemorrhage is an ophthalmic emergency. Early diagnosis and treatment are critical to ensure the best clinical outcome. Delayed treatment causes blindness and opportunistic infections can destroy the surrounding structure, a disaster.